Atopic dermatitis phenotype with early onset and high serum IL‐13 is linked to the new development of bronchial hyperresponsiveness in school children. Issue 5 (9th February 2016) - Lee, E.; Lee, S. H.; Kwon, J. W.; Kim, Y. H.; Cho, H. J.; Yang, S. I.; Jung, Y. H.; Kim, H. Y.; Seo, J. H.; Kim, B. J.; Kim, H. B.; Lee, S. Y.; et al.
Abstract: Background: Atopic dermatitis (AD) is characterized by a heterogeneous clinical spectrum, and some forms of AD are associated with the initial steps of allergic march. The aims of this study were to determine AD phenotypes in school‐age children and investigate their associations with the allergic march in each cluster. Methods: We included 242 children (6–8 years) with current AD from the Children's HEalth and Environmental Research study, a 4‐year prospective follow‐up study with 2‐year survey intervals. Latent class analysis was used. Serum IL‐13 and thymic stromal lymphopoietin (TSLP) levels at the time of enrollment were measured using ELISA. Results: We identified four current AD phenotypes in children, characterized as 'early onset with low atopy' (26.4% of the sample; group 1), 'early onset with high atopy and high eosinophil percentages' (48.3%; group 2), 'late onset with low atopy' (9.9%; group 3), and 'late onset with high atopy and normal eosinophils' (15.3%; group 4). Although groups 2 and 4 demonstrated high atopic burden, children in group 2 showed the persistence of AD and eosinophilia associated with a high prevalence of new cases of bronchial hyper‐responsiveness and asthma symptoms during follow‐up. The serum IL‐13 level was significantly increased in the early‐onset AD groups, but there was no significant difference in the serum TSLP levels across all four groups. Conclusion: An allergic march‐associated AD phenotype exists that is characterized by early onset of AD with its persistence, increased serum IL‐13 levels, high atopy, and a persistently increased blood eosinophil percentage.